EXPLORING THE CONCEPT OF TO PEMBUNI BELIEF AMONG THE NOSU’S PEOPLE FROM WILLIAM JOHNSTON'S MYSTICAL THEOLOGY PERSPECTIVE - Agustinus, Agustinus; Mettang, Marta (Balai Penelitian dan Pengembangan Agama Makassar, 2023)
This study delves into the intriguing world of